The Values of Physical Education from the Perspective of the Hadith - Akbar Yusuf; Arifuddin Ahmad; Muh. Sabir Maidin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Physical education plays a strategic role in developing students holistically by integrating physical, mental, social, moral, and spiritual dimensions. However, in educational practice, physical education is often narrowly focused on physical activities and sport skills, with limited integration of religious and moral values. This study aims to analyze the physical education values contained in the Hadith of the Prophet Muhammad (peace be upon him) and examine their relevance to modern physical education concepts. This research employed a qualitative approach using library research with a thematic Hadith analysis design. Data were collected from primary sources in the form of Hadiths and supported by secondary sources, including books and scientific journals related to physical education, health, and Islamic education. The findings indicate that the Hadith contains comprehensive physical education values, such as the importance of physical health and fitness, development of motor skills, discipline and consistency in physical activity, sportsmanship and moral character, and balance between physical and spiritual well-being. These values highlight that physical activity in Islam is not merely physical training but also a means of character formation and spiritual awareness. Furthermore, the study reveals a strong alignment between Hadith-based physical education values and modern physical education concepts that emphasize holistic development, health-oriented learning, character education, and lifelong active lifestyles. The study concludes that integrating Hadith-based values into physical education can strengthen its philosophical foundation and support the development of physically healthy, mentally resilient, and morally grounded individuals.